Global Citizenship Concepts Perspective Abdullah Ahmed An Naim - Aulia Rahman; Ahmad Barizi; Umi Sumbulah; Fachrurrazi Fachrurrazi; Moh. Buny Andaru bahy (International Journal of Islamic Khazanah, 2024)
Global Citizenship, rooted in the understanding and upholding human values, originated in the Western world and expanded into the Third World alongside globalization in various domains. Adopting a descriptive perspective, this research aims to comprehend and analyze Abdullah Ahmed An Naim's perspective on global citizenship. Utilizing a literature study at the philosophical level with a phenomenological approach method, this research explores the relationship between An Naim's thoughts and the concept of global citizenship, drawing from data sources in the form of books and journals. The data collection involves analyzing to synthesize existing sources. The study's findings reveal that according to Abdullah Ahmed An Naim, the concept of global citizenship involves reorienting the understanding of Sharia to respect the human rights of every citizen better. The expectation is that this research will contribute to formulating a new interpretation of the Islamic concept of global citizenship, emphasizing equality, peace without discrimination, and utmost respect for all citizens. In summary, this research provides insights into An Naim's perspective on global citizenship, shedding light on its implications for the Islamic framework and its potential contribution to fostering a more inclusive and egalitarian society.